Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Corrigendum to ‘The Derim Derim Dolerite, greater McArthur Basin, Australia: Using subsurface data to characterise a Mesoproterozoic magma plumbing system’ [Mar. Petrol. Geol., 169 (2024)] - Alice S. Hall; Simon Holford; Nick Schofield; Mark Bunch; Alan S. Collins; Morgan L. Blades; Darwinaji Subarkah (Marine and Petroleum Geology, 2024)

The Derim Derim Dolerite, greater McArthur Basin, Australia: Using subsurface data to characterise a mesoproterozoic magma plumbing system - Alice S. Hall; Simon Holford; Nick Schofield; Mark Bunch; Alan S. Collins; Morgan L. Blades; Darwinaji Subarkah (Marine and Petroleum Geology, 2024)

Biochar improves fertility in waste derived manufactured soils, but not resilience to climate change - Jennifer M. Rhymes; Daniel Evans; Giuliano Laudone; H. Kate Schofield; Ellen Fry; Mark F. Fitzsimons (Science of The Total Environment, 2024)

Nature and preservation of Late Jurassic breakup-related volcanism in the Carnarvon Basin, North West Shelf, Australia - Michael S. Curtis; Simon P. Holford; Mark A. Bunch; Nick Schofield (Marine and Petroleum Geology, 2023)

DeepVerge: Classification of roadside verge biodiversity and conservation potential - Andrew Perrett; Harry Pollard; Charlie Barnes; Mark Schofield; Lan Qie; Petra Bosilj; James M. Brown (Computers, Environment and Urban Systems, 2023)

The strong activity of noctilucent clouds at middle latitudes in 2020 - Peter Dalin; Hidehiko Suzuki; Nikolay Pertsev; Vladimir Perminov; Nikita Shevchuk; Egor Tsimerinov; Mark Zalcik; Jay Brausch; Tom McEwan; Iain McEachran; Martin Connors; Ian Schofield; et al. (Polar Science, 2023)

Current state of the art in continuous bioprocessing - Mark Schofield (Biotechnology Letters, 2018)

Does carbon limitation reduce nitrogen retention in soil? - H. Kate Schofield; Tim R. Pettitt; Alan D. Tappin; Gavyn K. Rollinson; Mark F. Fitzsimons (Environmental Chemistry Letters, 2018)

Reduced sensitivity for visual textures affects judgments of shape-from-shading and step-climbing behaviour in older adults - Andrew J. Schofield; Benjamin Curzon-Jones; Mark A. Hollands (Experimental Brain Research, 2017)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Letting Penguins Lead: Dynamic Modeling of Penguin Locations Guides Autonomous Robotic Sampling - Matthew Oliver; Mark Moline; Ian Robbins; William Fraser; Donna Patterson; Oscar Schofield (Oceanography, 2012)

Tolerance of nonindigenous cichlid fishes (Cichlasoma urophthalmus, Hemichromis letourneuxi) to low temperature: laboratory and field experiments in south Florida - Pamela J. Schofield; William F. Loftus; Robert M. Kobza; Mark I. Cook; Daniel H. Slone (Biological Invasions, 2010)

Dispersal of the Hudson River Plume in the New York Bight: Synthesis of Observational and Numerical Studies During LaTTE - Robert Chant; John Wilkin; Weifeng Zhang; Byoung-Ju Choi; Eli Hunter; Renato Castelao; Scott Glenn; Joe Jurisa; Oscar Schofield; Robert Houghton; Josh Kohut; Thomas Frazer; et al. (Oceanography, 2008)

Biological Responses in a Dynamic Buoyant River Plume - Mark Moline; Thomas Frazer; Robert Chant; Scott Glenn; Charles Jacoby; John Reinfelder; Jennifer Yost; Meng Zhou; Oscar Schofield (Oceanography, 2008)

Synergistic applications of autonomous underwater vehicles and the regional ocean modeling system in coastal ocean forecasting - Yi Chao; Zhijin Li; John D. Farrara; Mark A. Moline; Oscar M. E. Schofield; Sharanya J. Majumdar (Limnology and Oceanography, 2008)
The potential for using synergistic combinations of measurements from autonomous underwater vehicles (AUVs) and output from three‐dimensional numerical models for studying the central California coastal region is demonstrated. Two case studies are used to illustrate the approach. In the first, propeller‐driven AUV observations revealed a subsurface salinity minimum in northern Monterey Bay. A Regional Ocean Modeling System (ROMS) reanalysis of the three‐dimensional flow in the region suggested an offshore source for this water and particular propagation pathways from the south and west into the bay. In the second case study, the effectiveness of assimilating observations in improving the ROMS reanalysis fields is investigated. A significant improvement, especially in the salinity fields, is demonstrated through a single glider deployed outside the intensive observational domain. These results suggest that investigation of more sophisticated techniques for using data and models together is warranted. Such techniques include increasing model resolution in areas of interest identified by observing platforms and using model‐based “targeted observing” techniques to identify areas of uncertainty in the flow to guide placement of observational assets.

Alteration of the food web along the Antarctic Peninsula in response to a regional warming trend - Mark A. Moline; Hervé Claustre; Thomas K. Frazer; Oscar Schofield; Maria Vernet (Global Change Biology, 2004)
In the nearshore coastal waters along the Antarctic Peninsula, a recurrent shift in phytoplankton community structure, from diatoms to cryptophytes, has been documented. The shift was observed in consecutive years (1991–1996) during the austral summer and was correlated in time and space with glacial melt‐water runoff and reduced surface water salinities. Elevated temperatures along the Peninsula will increase the extent of coastal melt‐water zones and the seasonal prevalence of cryptophytes. This is significant because a change from diatoms to cryptophytes represents a marked shift in the size distribution of the phytoplankton community, which will, in turn, impact the zooplankton assemblage. Cryptophytes, because of their small size, are not grazed efficiently by Antarctic krill, a keystone species in the food web. An increase in the abundance and relative proportion of cryptophytes in coastal waters along the Peninsula will likely cause a shift in the spatial distribution of krill and may allow also for the rapid asexual proliferation of carbon poor gelatinous zooplankton, salps in particular. This scenario may account for the reported increase in the frequency of occurrence and abundance of large swarms of salps within the region. Salps are not a preferred food source for organisms that occupy higher trophic levels in the food web, specifically penguins and seals, and thus negative feedbacks to the ecology of these consumers can be anticipated as a consequence of shifts in phytoplankton community composition.

Watercolors in the Coastal Zone: What Can We See? - Oscar Schofield; Robert Arnone; Paul Bissett; Tommy Dickey; Curtiss Davis; Zoe Finkel; Matthew Oliver; Mark Moline (Oceanography, 2004)

Compound heterozygosity and nonsense mutations in the α1-subunit of the inhibitory glycine receptor in hyperekplexia - Mark I. Rees; Trevor M. Lewis; Behnaz Vafa; Colin Ferrie; Peter Corry; Fransesco Muntoni; Heinz Jungbluth; John B. Stephenson; Mike Kerr; Russell G. Snell; Peter R. Schofield; Michael J. Owen (Human Genetics, 2001)

Optical discrimination of a phytoplankton species in natural mixed populations - Gary J. Kirkpatrick; David F. Millie; Mark A. Moline; Oscar Schofield (Limnology and Oceanography, 2000)
Developing optical detection techniques for discriminating particular phytoplankon species in mixed assemblages has long been a goal of aquatic scientists. Previously, a processing algorithm for phytoplankton absorption spectra was reported that suggested detection of the red tide dinoflagellate Gymnodinium breve was possible. The algorithm evaluated the fourth derivative of the particulate absorption spectrum of an unknown sample and compared it to a standard fourth derivative spectrum for G. breve using a similarity index. We report here the first‐time application of this technique to the detection of G. breve in natural, mixed phytoplankton communities. Pigment and spectral absorption data were collected from natural blooms of G. breve in the eastern Gulf of Mexico. This dinoflagellate is the only species of phytoplankton in the Eastern Gulf of Mexico observed to contain the pigment gyroxanthin‐diester, and it appears in constant proportion to cellular chlorophyll a (Chl a) in G. breve . The in vitro absorption spectrum of gyroxanthin‐diester is nearly identical to other xanthophylls (including diadinoxanthin, lutein, and 199‐hexanoyloxyfucoxanthin) and is not singularly responsible for imparting a unique absorption signature. Quantifying gyroxanthin‐diester and Chl a allowed us to estimate the fraction of the biomass in mixed populations associated with G. breve . Subsequent regression of the G. breve similarity indexes to the G. breve biomass fractions yielded a significant linear correlation. Finally, the liquid waveguide capillary cell appears to be a promising technology for automating this technique.